Bio-characteristics, tissue expression of miR-375 in hypothalamic-pituitary-ovarian axis and its regulation in reproduction-related diseases - Saiyi Sun; Binglei Zhang; Wanhang Jia; Jiaxin Yang; Saiqiao Wang; Lu Zhao; Yan Ma; Qiujue Wu; Yuqin Wang (Scientific Reports)
Abstract Our study concentrated on the expression of miRNA-375 in the hypothalamic-pituitary-gonadal axis of female Hu sheep. The investigation involved cloning the precursor sequence of miR-NA-375, followed by comparison with database entries and subsequent Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. In our approach, we obtained ovaries, thalamus, cerebellum, brain, uterus, pituitary gland, hypothalamus, and pineal gland from fertile but nonpregnant Hu ewes. MiRNA extraction kit was used to extract miRNA from the above eight tissues. Real-time fluorescent quantitative polymerase chain reaction was used to evaluate the role of miR-375 in the hy-pothalamic-pituitary-gonadal axis. The results of miR-375 precursor sequence cloning were compared with those of Anopheles gambiae, Apis mellifera, Bos taurus, Drosophila melanogaster, Danio rerio, Fugu rubripes, Gallus gallus, Homo sapiens, Monodelphis domestica, Macaca mulatta, Mus musculus, Pan troglodytes, Rattus norvegicus, Tetraodon nigroviridis, Xenopus tropicalis miR-375 in miRBase database. It was found that oar-miR-375 was highly conserved. Notably, miR-375 expression in the pineal gland was significantly higher (p < 0.01) than that in the ovaries, thalamus, cerebellum, brain, uterus, pituitary gland, hypothalamus. The study also involved predicting miR-375 target genes. GO and KEGG enrichment analyses of these predicted target genes revealed that miR-375 is involved in 182 biological processes, affects 186 cellular components, and participates in 184 molecular functions. In terms of pathway enrichment, miR-375 was linked to nine pathways, including the Hippo, Wnt, and mTOR signaling pathways. This study has validated the interaction between miR-375 and its target gene FZD4, which can be recognized and bound to produce effects. These findings lead to the inference that miR-375 may play a crucial regulatory role in sheep reproduction through the Hippo pathway and Wnt pathway, laying a foundation for further exploration of miR-375’s role in this domain.